Computerised gymnastics judging scoring system implementation - an exploration of stakeholders' perceptions - Allen, E.; Fenton, A.; Parry, K. (Science of Gymnastics Journal, 2021)
Gymnastics is one of the original Olympic sports, subjectively judged by humans. Judging errors and bias can occur, resulting in medals being incorrectly awarded. The International Gymnastics Federation (FIG) with Fujitsu are introducing a computerised gymnastics judging support system (CGJSS), a technology aimed to enhance fairness and accuracy but there is very little literature evaluating this technology and perceptions. This project aimed to explore stakeholders` reactions at this critical time. Therefore, interviews were conducted with coaches, judges, media, former and current international gymnasts. The findings concurred with the literature review of judging problems with the current system, including bias and subjectivity. New findings show, among other things, that gymnasts` scores can differ depending on which round they compete in. The findings also suggest that the CGJSS would be a great innovation for gymnastics to improve credibility by removing bias and helping to make the sport more objective. However, the majority of the participants believed it could not judge the artistry element of the sport. Close monitoring of the effectiveness of the CGJSS is therefore required to identify enhancement and to ensure the investment produces fairer, more reliable and credible results. Successful implementation of the CGJSS could also allow it to be introduced into other subjectively judged sports.